Assessment of Mercury Level in Local Polish and Imported Honeys with Use of Direct Mercury Analyzer - Tomczyk, Monika; Kusibab, Julita; Zachara, Alicja; Dżugan, Małgorzata (Journal of Apicultural Science, 2023)
Mercury is a toxic metal which causes several serious health effects including kidney damage, anxiety depression and peripheral neuropathy, and because of its high volatility assessment in solid samples is problematic. In this study, forty-five samples of local Polish and imported honeys were analyzed by Direct Mercury Analyzer (DMA) for the determination of mercury content. The honey contamination was assessed regarding honey variety and country of origin. Hg level in all tested samples was found to not exceed the 0.81 μg/kg which was below 10% of the applicable law UE limit. Moreover, no statistically significant differences were found in the variety or geographical origin. The study concluded that the Direct Mercury Analyzer (DMA) instrument proved to be an excellent tool for screening mercury in honeys because of its simplicity, rapidity, low detection limit, accuracy and precision and no sample preparation.